2004
DOI: 10.2139/ssrn.531902
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy for Supply Chain Management Literature

Abstract: This paper presents a scheme for classifying the Supply Chain Management (SCM) literature. SCM is broadly defined to include all classical business functions and theoretic management disciplines which impacted this emerging field. Consequently, its literature is very disjoint and disparate. It transcends several academic disciplines and professions. This paper presents a way to define the field in its entirety and delineate all of its facets in a manner that is parsimonious yet discriminating. Sample articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Finally, this same approach could be used to investigate related concerns, such as supply‐chain taxonomies (e.g. Capar et al , ), and how they might evolve over time.…”
Section: Some Extensions and Emerging Research Questionsmentioning
confidence: 99%
“…Finally, this same approach could be used to investigate related concerns, such as supply‐chain taxonomies (e.g. Capar et al , ), and how they might evolve over time.…”
Section: Some Extensions and Emerging Research Questionsmentioning
confidence: 99%
“…A taxonomy has been offered for supply chains by Chandra and Tumanyan (2005), the generalization of planning problems in supply chain management. Capar et al (2004) introduce a supply chain management taxonomy structure that includes definitions. We adopt and extend the structure in their taxonomy in our supply chain attributes dimension.…”
Section: Taxonomies Of Supply Chains and Innovationsmentioning
confidence: 99%
“…Secondly, it creates a taxonomy of supply chain attributes that show how supply chains differ from each other. The study analyzes case studies reported in literature and in the Supply Chain Innovation Award (SCIA), and taxonomy papers (Capar et al, 2004) to construct an extensive classification of attributes of supply chains. Then, as the final dimension, the study classifies the innovations based on their attributes.…”
Section: Taxonomy For Supply Chain Innovationsmentioning
confidence: 99%
“…In our example, triangular variables have been adopted to describe the uncertain parameters of model (3) because it simplifies the operations on fuzzy sets. It is defined by three bounds [i,m, U], where / is a lower bound, m is a mean value and u is an upper bound.…”
Section: Numerical Examplementioning
confidence: 99%
“…Some literature reviewed fuzzy models in supply chain (SC) [3,4]. For instance, about fuzzy pricing, Chen and Wang [5] forecasted product price and order quantity with fuzzy variables, and put forward many methods of forecast; Bernhard et al [6] research monopoly's pricing for products without constraints under fuzzy information.…”
Section: Introductionmentioning
confidence: 99%